Critical literacy context, research, and practice in the K-12 classroom - Patel Stevens, Lisa.; Bean, Thomas W.; Sage eBooks (Thousand Oaks, [Calif.] ; London : SAGE, 2007)
Comprised of chapters that make use of clear explanations of the tenets of critical literacy, the context of literacy pedagogy in the US, and classroom examples, this text focuses on what can be learned about the theory of critical literacy from implementation and what practice can learn from theory.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Critical pedagogy -- United States; Literacy -- Social aspects -- United States; Electronic books